Race, culture, and identity: An exploration of Dominican identity and race-based discriminations against Haitians in the Dominican Republic - Torres, Jonathan Rentas (Université d'Ottawa | University of Ottawa, 2017)
In the Dominican Republic Haitians have historically been discriminated against because of their “negritud” (blackness) and are not seen as part of Dominican society. Social media, popular culture, and the state’s governmental structure have all built them as a historical threat. This can be traced as early as 1822 when Haitians (predominantly of African origin) sought to unify the island of Hispaniola by invading the Dominican Republic (called Santo Domingo at the time and predominantly composed of persons of mix “race” origins) (Espy, 2015). The Dominican Republic and Haiti share the Caribbean island of Hispaniola and racial-ethnic tensions are a common theme in the socio-political discourse of both countries. This “racial” discrimination is known in the DR as “anti-haitianismo” (to be against Haitians). This concept was expanded during the dictatorship of Rafael Trujillo that lasted from 1931 to 1961. It identifies Haitians as foreign, uneducated, violent and other pejorative terms that essentially classified them as an underclass. “In the Dominican Republic, European and indigenous heritages in the country have been celebrated at the expense of an African past” (Howard, 2001, p. 1). It is important to understand how in the Dominican Republic this belief deeply influenced the Dominican elites in their search for a “whiter” country but also how Human Rights organizations in the country continue to work to defy these trends and the way the law and the state structure marginalizes Haitian migrants and their descents. Keywords: Race, culture, identity, anti-haitianismo, education.